Instagram vs TikTok: Which Platform is More Effective for Enhancing SMEs Performance? - Soelaiman, Lydiawati; Herwindiati, Dyah Erny; Payangan, Otto Randa (Jurnal Komunikasi, 2023)
Digital transformation makes social media one of the infrastructures that introduces effective performance changes for MSMEs. Referring to the concept of the research model built based on the Technology Organization Environment (TOE) theory, tThere are three basic factors that need to be considered by MSMEs in adopting social media, namely compatibility, cost-effectiveness and interactivity. This study aims to compare the effects of compatibility, cost-effectiveness, and interactivity on SME performance between the social media platforms Instagram and TikTok. A comparative study was utilized in this research to examine the impact of variables on the Instagram and TikTok social media platforms. The sample consisted of 200 SMEs was selected through purposive sampling. The data were analyzed using Partial Least Squares Multigroup Analysis (PLS-MGA). The study's results indicate that compatibility and interactivity significantly influence the adoption of both Instagram and TikTok social media platforms. On the other hand, the cost-effectiveness variable only affects the adoption of the TikTok social media platform but does not significantly affect the adoption of Instagram. This study also found that only interactivity significantly differs in adopting social media platforms between Instagram and TikTok. The results showed that Instagram social media provides greater interactivity than TikTok. The other two variables, compatibility, and cost-effectiveness do not significantly differ. Furthermore, the study also found a positive influence of using both Instagram and TikTok social media platforms on SMEs' performance.